Os instrumentos do coordenador pedagógico para coordenar a formação continuada dos professores na unidade escolar: “o projeto especial de ação” e “o programa a rede em rede: a formação continuada na educação infantil” no município de São Paulo - Andrade, Elaine Cristina Marena (2010)
A major advance of the public policies in Brazil was to consider the early childhood education (0 to 5 yeas) as the first stage of basic education, and include day care centers in the municipal sistem of education, this way treating the care and education as inseperable concepts. With this advance, apperead the concern about the training of teachers working in early childhood education and, also, the necessity of developing public policy programs for teacher training. In this context, I started to observe the network of the Special Action Project and the Network Project: continued formation in kindergarten, the work of teachers daily in early childhood education and I found, among many issues, one of great importance: how the continued formation of teachers of early childhood education has contributed to the updating of the pedagogical practice? The objectives of this research are to analyze the performance of both the project and educational program in the school routine, in Kindergarten, in due to identify the presence, in the teaching practice, of the policies for teacher education intentions, and to analyze the teacher evaluation on teacher education policies, proposed by the Municipality of São Paulo. The methodological procedures are quantitative approach, questionnaire to 21 teachers and 02 administrators, and qualitative approach, semi-structural interview, with the participation of 03 teachers and documentary analysis, over the period from 2005 to 2008 of the school unit. The Pedagogical Coordinator needs to consider that the teacher is unique, complex, with his own decisions, that transforms and is transformed by others. The new pedagogical knowledge may become a part of the teaching practice when they become articulated with the real needs and desires of teachers. The important issue is to ensure that the Academic Coordinator has moments destined to follow the teaching practice, as well as the moments of tracking continuing education, at collective times. Therefore, the academic coordinator will have greater proximity of the teacher's pedagogical actions, doubts, concerns, educational needs, in other words, will have the opportunity to perform an individual intervention. This may contribute to the advance of teaching